Effects of xylitol dehydrogenase (XYL2) on xylose fermentation by engineered Candida glycerinogenes. (23rd March 2017) - Zong, Hong; Zhang, Cheng; Zhuge, Bin; Lu, Xinyao; Fang, Huiying; Sun, Jin
Abstract: Efficient bioconversion ofd ‐xylose into various biochemicals is critical for lignocelluloses application. Candida glycerinogenes, expressing the xylitol dehydrogenase ( XYL2 ) gene, has the ability to produce glycerol from xylose entered into pentose phosphate pathway. In this study, we demonstrate that low expression levels of the XYL2 gene derived from Scheffersomyces stipitis in C. glycerinogenes is a major bottleneck in efficient xylose fermentation. Through a metabolic engineering approach using an integrative expression, XYL2 was identified as an overexpression target for improving xylose metabolism. Two recombinant strains with XYL2 overexpression were constructed to ferment a mixture of glucose and xylose simultaneously in batch fermentation. Compared with C. glycerinogenes (wild type), glycerol production from xylose by C. glycerinogenes (PURGAPX2) and C. glycerinogenes (PURGPDX2) was increased by 94.5% and 103.3%, respectively. It was also found that additional overexpression of XYL2 under the control of strong promoters in a xylose‐fermenting strain not only reduced xylitol accumulation but also increased glycerol yields. As the expression levels of XYL2 increased, the glycerol yields gradually improved from 30.6 to 63.3 g/L, whereas the xylitol yields significantly decreased from 38.7 to 19.9 g/L. These results suggest that strong expression of XYL2 is a necessary condition for developing efficient xylose‐fermenting strains.